Multi-wavelength laser tuning based on cholesteric liquid crystals with nanoparticles - Chen, Sheng-Chieh; Lin, Jia-De; Lee, Chia-Rong; Hwang, Shug-June (My University, 2016)
A controllable multi-wavelength laser from a dye-doped cholesteric liquid crystal (DDCLC) cell is demonstrated by incorporating self-assembled polyhedral oligomeric silsesquioxane (POSS) nanoparticles (NPs). Multi-wavelength lasing emission is achieved by formation of multiple planar domains; this formation is dominantly influenced by the vertical alignment of NP clusters adsorbed on the substrate surface through a rapid thermal annealing process. The multi-wavelength lasing peaks are generated through the resultant effect of multiple longitudinal resonant modes of a Fabry-Perot etalon between the cell substrates and the amplification of fluorescence photons with the resonant wavelengths within the broadening long-wavelength edge of the reflection band of the multi-domain CLC. The amount of multi-wavelength lasing peaks can be controlled by changing the POSS NP concentration and the cooling rate of the cell. Furthermore, thermo-reversible control of the multi-wavelength lasing emission can be attained by controlling the thermally induced phase separation process of the POSS/DDCLC cell via a heating/cooling cyclic process.
Keywords: cholesteric liquid crystal; nanoparticles; laser; thermally-induced phase separation